EDUKASI PENETAPAN WAKTU HENTI OBAT HEWAN BAGI PETERNAK SAPI PERAH DI KABUPATEN SIDOARJO, JAWA TIMUR - Mochamad Lazuardi; Bambang Hermanto; Tjuk Imam Restiadi (Jurnal Layanan Masyarakat (Journal of Public Services), 2020)
Food safety and the phenomenon of antimicrobial resistance have caused world problems since the beginning of 2019, while the abuse and use of antibiotic problems in fresh animal origin products (PSAH) are still common. The purpose of this training activity is to provide direct competency strengthening for farmers who are closely related to the use of antibiotics where PSAH obtained will be directly related to human health. A total of 50 dairy farmers were conducted training using the method of learning by doing and doing by learning using 3 stages of activities, namely (1) strengthening competencies face to face, (2) continued training in counting downtime of veterinary medicines using props, ending the application of tetracycline residue examination at PSAH and examples of milk residues. The results of the training show that there is mastery of training materials by the average farmer farmers controlled by 85%.AbstrakKeamanan pangan dan fenomena antimicroba resistance menjadikan persoalan dunia sejak awal tahun 2019, sementara penyalahgunaan dan penggunasalahan antibiotika pada produk segar asal hewan (PSAH) masih sering terjadi. Tujuan kegiatan pelatihan ini adalah untuk memberikan penguatan kompetensi langsung terhadap peternak yang erat kedekatannya dengan penggunaan antibiotika dimana PSAH yang diperoleh akan langsung berhubungan dengan kesehatan manusia. Sejumlah 50 peternak sapi perah dilakukan pelatihan menggunakan metode learning by doing dan doing by learning menggunakan 3 tahapan kegiatan yaitu (1) penguatan kompetensi secara tatap muka, (2) dilanjutkan pelatihan penghitungan waktu henti obat hewan menggunakan alat peraga, diakhiri penerapan pemeriksaan residu tetrasiklin pada PSAH dan contoh adanya residu apada susu. Hasil pelatihan menunjukkan terdapat penguasaan materi pelatihan oleh petani peternak rerata dikuasai 85%.